2020
DOI: 10.1002/chem.201905712
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Transfer‐Mediated Domino Cyclisation Reaction to Access (Spiro)Quinazolinones

Abstract: A radical domino cyclisation reaction of N‐cyanamide alkenes, mediated by hydrogen atom transfer (HAT) has been developed. This method, using PhSiH3 and catalytic Fe(acac)3, allows for the synthesis of challenging (spiro)quinazolinone scaffolds from simple, tractable (hetero)aryl carboxylic acid and cyanamide building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…218 The reaction proceeds through a radical cascade, beginning with generation of the aryl radical from the diazonium tetrafluoroborate (225). Attack of the aryl radical onto the sulfur in the isothiocyanate (226) results in an α-(arylthio)imidoyl radical (228). Cyclization onto the nitrile afforded an iminyl radical (229), which underwent cyclization onto the arene moiety furnishing 227 in 80% yield.…”
Section: Indirect Generation Of Iminyl Radicals From Nitriles In Casc...mentioning
confidence: 99%
“…218 The reaction proceeds through a radical cascade, beginning with generation of the aryl radical from the diazonium tetrafluoroborate (225). Attack of the aryl radical onto the sulfur in the isothiocyanate (226) results in an α-(arylthio)imidoyl radical (228). Cyclization onto the nitrile afforded an iminyl radical (229), which underwent cyclization onto the arene moiety furnishing 227 in 80% yield.…”
Section: Indirect Generation Of Iminyl Radicals From Nitriles In Casc...mentioning
confidence: 99%
“…[36] To expand the scope of synthetic strategies toward preparation of this useful scaffold Turner, Hirst and Murphy developed a radical domino cyclization of Ncyanamides 88 catalyzed by Fe(acac) 3 in synthesis of spiroquinazolinones 89 (Scheme 24). [37] Synthesis of this challenging spirocyclic scaffolds proceeds in mild reaction conditions and under air atmosphere produce final spirocyclic compounds in reasonable yields (up to 74%). A practical aspect of oxidative radical iron triggered cyclization that allows the facile construction of highly substituted spirocycles has been recently presented by Jahn group in total synthesis of ent-asperparaline C (Scheme 26).…”
Section: Iron-mediated Spirocyclizationsmentioning
confidence: 99%
“…To expand the scope of synthetic strategies toward preparation of this useful scaffold Turner, Hirst and Murphy developed a radical domino cyclization of N ‐cyanamides 88 catalyzed by Fe(acac) 3 in synthesis of spiroquinazolinones 89 (Scheme 24). [37] Synthesis of this challenging spirocyclic scaffolds proceeds in mild reaction conditions and under air atmosphere produce final spirocyclic compounds in reasonable yields (up to 74%).…”
Section: Iron‐mediated Spirocyclizationsmentioning
confidence: 99%
“…Based on the hydrogen atom transfer (HAT)-mediated cyclizations of nitriles reported, 11 in 2020, Murphy's group disclosed a radical domino cyclization reaction of N -cyanamide alkenes 7 through the HAT process to access spiroquinazolinone 2,3-fused five-membered ring compounds 8 in good yields (Scheme 4). 12 It was found that the reaction could be carried out with 10 mol% of Fe(acac) 3 as a catalyst and 1.05 equiv. of PhSiH 3 as a reductant in i-PrOH at 50 °C under an air atmosphere.…”
Section: Difunctionalization Of Alkenes To Prepare 23-fused Quinazoli...mentioning
confidence: 99%